Planning and management of environmental education to promote educator's environmental awareness and pro-environmental behaviour - Mami Miyasaka; Shin Honda (Springer, 2024)
Abstract The increased burden on educators to promote environmental education has recently attracted research interest. Since environmental knowledge has insignificant direct effects on pro-environmental behaviour, it is important to devise effective teaching methods to reduce the burden on educators and promote environmental conservation. In this study, we examined whether the planning and practice of educating others promoted environmental consciousness in the educators. Twenty-four and twenty-two university students participated in the study as part of an experimental and active control group, respectively. The experimental group was asked to plan and manage events meant to educate children about the environment and help them feel comfortable in nature. As a result, compared to the beginning of the study, the experimental group participants exhibited increased environmental consciousness. This improvement could be attributed to the fact that the participants possibly altered their behaviour towards the environment, consistent with the nature conservation practices they presented to the children participating in the abovementioned events. These findings highlight how planning and managing environmental conservation events for others could influence and improve individuals' environmental consciousness.